16th seduction [compact disc, abridged] - Patterson, James, 1947-; Paetro, Maxine (Patterson, James, 1947- Women's murder club., 2017)
Still reeling from her husband's betrayal, Lindsay Boxer investigates a wave of possibly unnatural heart attacks claiming the lives of seemingly unrelated victims while assisting the prosecution of a bomber with a hostile defense team.